Assessing the Impact of Pricing, Service, and Product Quality on Telkomsel Customer Loyalty - Marchela Indah Atrisia; Budiastuti Fatkar; Ana Tiara; Sherly Astuti (Master of Management, School of Business and Management, Petra Christian University, 2024)
Amidst ongoing economic development and rapid technological progress, businesses face the challenge of not solely focusing on sales to ensure profitability. Internet service providers, in particular, Telkomsel, must deliver exceptional services to thrive in a competitive landscape and maximize profits. This study examines the influence of pricing, service quality, and product quality on customer loyalty towards Telkomsel products, focusing on 8th semester students of the Faculty of Economics and Business at Islamic University Sheikh - Yusuf Tangerang. Employing a descriptive quantitative approach, data were gathered from 80 respondents through purposive sampling and distributed via Google Forms. Multiple linear regression analysis was utilized to test the relationship between the variables, with further examination through t-test, F-test, and coefficient of determination analysis. The findings indicate a positive and significant relationship between price, service quality, product quality, and customer loyalty. Moreover, the coefficient of determination analysis confirms that these factors collectively contribute to customer loyalty. Thus, the study concludes that price, service quality, and product quality significantly influence customer loyalty toward Telkomsel products.